2017
DOI: 10.1186/s12891-017-1646-6
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of posterior cruciate ligament leads to radial displacement of the medial meniscus

Abstract: BackgroundTo explore the association between the rupture of posterior cruciate ligament (PCL) and the radial displacement of medial meniscus under the conditions of different flexion and various axial loads.MethodsThe radial displacement value of medial meniscus was measured for the specimens of normal adult knee joints, including 12 intact PCLs, 6 ruptures of the anterolateral bundle (ALB), 6 ruptures of the postmedial bundle (PMB), and 12 complete ruptures. The measurement was conducted at 0°, 30°, 60°, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This could partially explain limitation of extreme flexion (73.2% of patients) and extension (19.5% of patients) before operation, and range of motion improved greatly after meniscal tear being treated with either partial meniscectomy or meniscal repair. Zhang et al [ 25 ] reported PCL injury resulted in radial displacement of the medial meniscus which may lead to degenerative changes of meniscus. A study by Gao et al [ 26 ] revealed human cadaveric knee with PCL transection had a higher strain on whole medial meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…This could partially explain limitation of extreme flexion (73.2% of patients) and extension (19.5% of patients) before operation, and range of motion improved greatly after meniscal tear being treated with either partial meniscectomy or meniscal repair. Zhang et al [ 25 ] reported PCL injury resulted in radial displacement of the medial meniscus which may lead to degenerative changes of meniscus. A study by Gao et al [ 26 ] revealed human cadaveric knee with PCL transection had a higher strain on whole medial meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral meniscus injury is more common in acute injuries, with or without cruciate ligament injury. [11][12][13] The injury of the medial meniscus, especially the injury of the posterior horn of the medial meniscus. It's common in older people, but it's also common in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…The menisci play an important role in protecting the cartilage surfaces of the knee joint from axial loads [ 9 ]. Recently, the treatment of the PRMM is not uniform including conservative treatment, meniscectomy, and meniscus repair [ 10 13 ].…”
Section: Discussionmentioning
confidence: 99%